2023
DOI: 10.1186/s40814-023-01299-x
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of team care for women seeking to plan a vaginal breech birth (OptiBreech 1): an observational implementation feasibility study in preparation for a pilot trial

Shawn Walker,
Emma Spillane,
Kate Stringer
et al.

Abstract: Background OptiBreech Care is a care pathway for breech presentation at term, including where chosen, physiological breech birth attended by professionals with advanced training and/or proficiency. We aimed to assess the feasibility of implementing OptiBreech team care prior to proceeding with a planned pilot randomised controlled trial. Methods Our design was an observational implementation feasibility assessment across England and Wales, January … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Across three studies, one serious adverse neonatal outcome has been reported (0.5%). [3][4][5] This is very near to the rate of adverse outcomes observed among low-risk women planning cephalic (head-first) births in the UK. Neonatal admission rates have been below 5%, similar to rates for all term births in the UK.…”
Section: Dear Editormentioning
confidence: 85%
See 1 more Smart Citation
“…Across three studies, one serious adverse neonatal outcome has been reported (0.5%). [3][4][5] This is very near to the rate of adverse outcomes observed among low-risk women planning cephalic (head-first) births in the UK. Neonatal admission rates have been below 5%, similar to rates for all term births in the UK.…”
Section: Dear Editormentioning
confidence: 85%
“…The complex intervention being tested, OptiBreech collaborative care, has been built up from over a decade's worth of research into howin the current conditions you describepractitioners acquire VBB skill and experience. [3][4][5] As you say, the conditions that (arguably) enabled this in the past are now non-existent. Different times call for different thinking and different strategies.…”
Section: Dear Editormentioning
confidence: 99%
“…The second evaluated the feasibility of implementing Opti-Breech collaborative team care for planned VBBs 18 . In this study, among 82 planned VBBs, one serious adverse outcome (same composite, 1.2%) occurred.…”
Section: Discussionmentioning
confidence: 99%
“…We feel our results so far are due to strong qualitative work to develop the programme theory for the OptiBreech collaborative care model. Our logic model was developed and refined through: frequent and meaningful PPIE activities; systematic reviews to establish background, questions and women's experiences 8,22,33 ; Delphi consensus methods, including clinicians and service users, on core competencies and important outcomes 4,16,24,25,34 ; grounded theory methods to describe how clinicians learn breech skills 2,3 ; feasibility work to prepare for a substantive clinical trial 1,18 ; and a pilot randomised trial 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation